2006
DOI: 10.2135/cropsci2006.01-0046
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Cultivar Performance on Certified Organic Fields in Minnesota and North Dakota

Abstract: Synthetic agrichemicals are used to minimize nutrient deficiencies and pests when developing and selecting modern small-grain cultivars. Some farmers believe that modern cultivars are not adapted to environments without these inputs, and old cultivars should be grown. Our objective was to determine the adaptability of spring wheat (Triticum aestivum L.) cultivars for production in certified organic environments. A single seed lot for 15 cultivars and two seed lots each for two others were used to establish 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 16 publications
3
34
0
1
Order By: Relevance
“…While his work shows that conventionally-bred lines can perform well under organic management, it does not indicate that conventionally-selected lines are the best for organic systems. Carr concludes that "modern cultivars of hard red spring wheat that were developed and selected using synthetic agrichemicals are adapted to environments under certified organic management" (Carr et al 2006). Stephen Jones, in his organic wheat breeding program at Washington State University, uses older varieties to identify and supply high-quality baking and milling traits that can then be used to improve disease-resistant modern varieties for organic production systems.…”
Section: Other Issuesmentioning
confidence: 99%
“…While his work shows that conventionally-bred lines can perform well under organic management, it does not indicate that conventionally-selected lines are the best for organic systems. Carr concludes that "modern cultivars of hard red spring wheat that were developed and selected using synthetic agrichemicals are adapted to environments under certified organic management" (Carr et al 2006). Stephen Jones, in his organic wheat breeding program at Washington State University, uses older varieties to identify and supply high-quality baking and milling traits that can then be used to improve disease-resistant modern varieties for organic production systems.…”
Section: Other Issuesmentioning
confidence: 99%
“…For highly heritable traits where selection can be imposed in the early stages on a single plant or small plot basis, indirect selection, i.e. selection in an environment different from the target environment, can even lead to higher selection efficiency than direct selection (Hill et al 1998 The selection strategies for low-input conditions imposed by Hänsel and Fleck (1990) and Spanakakis and Röbbelen (1990) have led to varieties adapted to OA in several European countries together with new conventional varieties that perform best in OA in the US (Carr et al 2006).…”
Section: Current Status Of Cereal Breeding For Organic Agriculturementioning
confidence: 99%
“…New genetic material from other farming systems has to be introduced continuously into OA in order not to lose genetic variability (Carr et al 2006). The highest possible variability of varieties for OA can be assured by extending the choice to varieties developed within all three breeding strategies, BFCA, BFOA and OPB.…”
Section: Current Status Of Cereal Breeding For Organic Agriculturementioning
confidence: 99%
“…Several studies report differences in the performance of wheat cultivars in organic and conventional management systems, with some cultivars better suited to organic management in northern North America (Carr et al 2006;Mason et al 2007c;Nass et al 2003). Przystalski et al (2008) found specific cultivars exhibiting cross-over interactions between management systems despite high genetic correlations between systems.…”
Section: Introductionmentioning
confidence: 99%